Effects of different warm-up protocols and no warm up on speed performance among football players - Hashbullah, I.; Mardiana, M.; Hosni, H.; Azidin, R. (International Conference on Science and Social Research (CSSR), 2010, 2010)
The purpose of this study was to investigate the effects of different warm-up protocols and no warm up on speed performance among football players. Twenty five football players aged 15.6 ± 0.70 years each participated in this study. One initial study familiarization session has been conducted. Three randomly assigned experimental test sessions have been conducted in three consecutive days a week which consisting no warm-up with 3 minutes time interval between trial, 15 minutes static warm-up and 10 min dynamic warm-up. All test sessions were separated by at least 48 hours and done in the morning at eight a.m. Performance testing consist 40m sprint for speed test. One-Way ANOVA on the warm-up conditions showed a significant difference among the three different protocols (F=9.782; p=0.02). Post Hoc comparisons revealed that participant sprint performance was faster following no warm-up (5.386 + 0.13907 sec) than in static warm-up (5.5740 + 0.20601sec) and dynamic warm-up (5.5440 + 0.21397 sec). This study indicated that speed performance in 40m sprint was better without performed a warm-up compared to static and dynamic warm-up. Moreover, the static and dynamic warm-up diminished the speed performance. An intense warm-up may result in decrease in performance because of the reduction in high-energy phosphates.